The Existence of Smart Contracts in Electronic Agreements: A Civil Juridical Review - Khuan, Hendri; Anam, Ach Dlofirul (PT. Anagata Sembagi Education, 2025)
The development of blockchain technology has given birth to smart contracts as a new instrument in electronic agreements that are executed automatically by computer programs based on agreed conditions. The autonomous, transparent, and irreversible characteristics of smart contracts present a challenge to the classical principles of Indonesian civil law, especially Article 1320 of the Civil Code which regulates the conditions for the validity of agreements. The main problem lies in the fulfillment of the elements of free will and agreement, especially when consent is given to a code that is not fully understood by parties without a technological background. Although Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law) recognizes electronic documents as legal evidence, there are no explicit provisions governing the validity, legal responsibility, and dispute mechanisms related to smart contracts. This study uses a normative juridical method with a statutory and conceptual approach to examine the existence of smart contracts in the Indonesian legal system. It is necessary to reinterpret and harmonize civil law with technological developments so that smart contracts are not only legally valid, but also fair and provide adequate legal protection. Without regulatory reform, legal certainty and substantive justice in the use of smart contracts have the potential to be neglected.